Preoperative nutritional status as a predictor of postoperative overall survival in abdominal tumor surgery: a systematic review and meta-analysis - Su, Zhaoyin; Lin, Yifeng; Li, Molan; Yang, Yanyan; Chen, Xiaohan; Zhu, Yifu; Mo, Yifan; Huang, Zhirui; Liu, Yatao; Michael, Nerlich (Frontiers in Surgery, 2025)
BackgroundAbdominal tumors, including those in the stomach, colon, pancreas, and gallbladder, significantly impact global morbidity and mortality. Surgical resection is the primary treatment, but postoperative outcomes and long-term survival are often affected by factors such as preoperative nutritional status. Malnutrition is common in these patients, making its management crucial for improving outcomes. This systematic review and meta-analysis aim to consolidate evidence on the role of preoperative nutritional status in postoperative survival for patients undergoing abdominal tumor surgery, offering insight into its prognostic value.MethodsA systematic literature search was conducted using electronic databases to report the impact of the preoperative nutritional status on OS (overall survival) of patients with abdominal tumor surgery as of January 1st, 2025. The hazard ratio (HR) with a 95% confidence interval (CI) was used to evaluate the impact of the preoperative nutritional status on OS.ResultsA total of 32 studies involving 10352 patients were included in the meta-analysis. The results (pooled HR: 1.61, 95% CI: 1.49–1.73, I² = 43.0%, p < 0.001) indicated that preoperative malnutrition is significantly associated with poorer OS. Subgroup and meta-regression analyses based on methods of nutritional status assessment, country, sample size, study design, follow-up duration, analytical model, and tumor type all showed a consistent association between preoperative malnutrition and worse OS. The robustness of these pooled results was further verified through sensitivity analysis. Additionally, the heterogeneity of pooled HR of OS was attributed to differences in study designs, as indicated by meta-regression analysis (p = 0.005). Funnel plots did not show significant publication bias.ConclusionBased on existing evidence, the preoperative nutritional status is a valuable predictor of postoperative OS in patients with abdominal tumor surgery.Systematic Review RegistrationPROSPERO CRD420251008979.